Sonographic evaluation of the shoulder in asymptomatic elderly subjects with diabetes - Salini Vincenzo; Schiavone Cosima; Abate Michele (BMC Musculoskeletal Disorders, 2010)
Abstract Background The prevalence of rotator cuff tears increases with age and several studies have shown that diabetes is associated with symptomatic shoulder pathologies. Aim of our research was to evaluate the prevalence of shoulder lesions in a population of asymptomatic elderly subjects, normal and with non insulin - dependent diabetes mellitus. Methods The study was performed on 48 subjects with diabetes and 32 controls (mean age: 71.5 ± 4.8 and 70.7 ± 4.5, respectively), who did not complain shoulder pain or dysfunction. An ultrasound examination was performed on both shoulders according to a standard protocol, utilizing multiplanar scans. Results Tendons thickness was greater in diabetics than in controls (Supraspinatus Tendon: 6.2 ± 0.09 mm vs 5.2 ± 0.7 mm, p < 0.001; Biceps Tendon: 4 ± 0.8 mm vs 3.2 ± 0.4 mm, p < 0.001). Sonographic appearances of degenerative features in the rotator cuff and biceps were more frequently observed in diabetics (Supraspinatus Tendon: 42.7% vs 20.3%, p < 0.003; Biceps Tendon: 27% vs 7.8%, p < 0.002). Subjects with diabetes exhibited more tears in the Supraspinatus Tendon (Minor tears: 15 (15.8%) vs 2 (3.1%), p < 0.03; Major tears: 15 (15.8%) vs 5 (7.8%), p = ns), but not in the long head of Biceps. More effusions in subacromial bursa were observed in diabetics (23.9% vs 10.9%, p < 0.03) as well as tenosynovitis in biceps tendon (33.3% vs 10.9%, p < 0.001). In both groups, pathological findings were prevalent on the dominant side, but no difference related to duration of diabetes was found. Conclusions Our results suggest that age - related rotator cuff tendon degenerative changes are more common in diabetics. Ultrasound is an useful tool for discovering in pre - symptomatic stages the subjects that may undergo shoulder symptomatic pathologies.